Defluorination adsorbent as well as preparation method and application thereof
By combining zirconia crystals with polymer frameworks and using drip molding or granulation processes, the zirconia crystals are evenly dispersed in the polymer carrier, the problem of the existing fluorine-depleting ion exchange resins in the adsorption process of zirconia crystals is solved, and the adsorption stability and service life are significantly improved.
Patent Information
- Application Number
- CN202411909692.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-07
AI Technical Summary
The existing fluorine-depleting ion exchange resins are prone to 'slag-drop-drop-drop-drop-drop-drop-drop-drop-drop-drop-drop-drop-drop-free adsorbents and short service life.
By combining the zirconia crystals with the polymer framework, the zirconia crystals are uniformly dispersed in the polymer carrier by using drip molding or granulation processes to form a new fluorine-removing adsorbent.
It significantly improves the adsorption stability of zirconia, extends the service life of the adsorbent, and there is almost no 'slag-drop' phenomenon during the repeated adsorption and desorption cycle.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent preparation, and in particular to a defluorination adsorbent and a preparation method and application thereof. Background Art
[0002] Since the fluorine removal ion exchange resin mainly utilizes the adsorption capacity of the ion exchange resin to zirconium ions, the zirconium ions are fixed on the ion exchange resin in the form of complexation, and then under alkaline conditions and certain post-treatment, the zirconium ions on the resin are converted into zirconium oxide crystals that have the ability to attract fluorine. The present invention discloses an adsorbent that has a good fixation effect on zirconium oxide crystals based on the good adsorption of zirconium oxide crystals to fluorine.
[0003] When the above-mentioned ion exchange resin converts zirconium ions into zirconium oxide crystals with adsorption capacity for fluorine, the adsorbent often "degrades", that is, the ion exchange resin has a weak adsorption capacity for a certain amount of zirconium oxide crystals, causing part of the zirconium oxide to fall off, and continuous degrading will also occur during the adsorption regeneration of the resin. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a defluorination adsorbent and a preparation method and application thereof. The present invention is to solve the above-mentioned slagging problem and ensure the stability of the defluorination adsorbent, extend the life of the adsorbent, and thus design a defluorination adsorbent with a longer service life.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a defluorination adsorbent, comprising the following steps:
[0007] 1) mixing zirconium oxychloride with hydrochloric acid solution and water, adjusting the pH value to 9.0 with sodium hydroxide solution at a drip rate of 10 mL / min, and drying to obtain zirconium oxide crystals;
[0008] The volume ratio of the zirconium oxychloride mass to the volume of the hydrochloric acid solution and the volume of water is 256 g:240 mL:500 mL;
[0009] 2) mixing an organic solvent with a polymer to obtain a polymer solution;
[0010] The polymer includes one or more of polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate and polysulfone;
[0011] The volume ratio of the organic solvent to the mass ratio of the polymer is 200 mL:50 g;
[0012] 3) mixing the zirconium oxide crystals obtained in step 1) with the polymer solution obtained in step 2) to obtain a mixture, and subjecting the mixture to drop molding or granulation to obtain a defluorination adsorbent;
[0013] The mass ratio of the zirconium oxide crystals to the polymer in step 2) is 2 to 50:5.
[0014] Preferably, the mass percentage of the hydrochloric acid solution in step 1) is 30%.
[0015] Preferably, the mass percentage of the sodium hydroxide solution in step 1) is 30%.
[0016] Preferably, the temperature adjusted in step 1) is 60°C.
[0017] Preferably, the organic solvent in step 2) comprises acetone and / or dimethylformamide.
[0018] Preferably, the step 3) drop molding comprises the following steps: passing the mixture into water through a pinhole with a diameter of 0.5 mm, and obtaining a defluorination adsorbent after washing and drying.
[0019] Preferably, the step 3) granulation comprises the following steps: forming the mixture into spherical particles with a particle size of 0.5 to 1 mm, and then solidifying, washing and drying to obtain a defluorination adsorbent.
[0020] Preferably, the solidification conditions include: mixing the spherical particles with a poor solvent and solidifying them.
[0021] The present invention also provides a defluorination adsorbent prepared by the preparation method described in the above technical solution.
[0022] The present invention also provides the use of the defluorination adsorbent described in the above technical solution in improving the stability of zirconium adsorption by the adsorbent.
[0023] The mechanism by which the defluorination adsorbent provided by the present invention improves the adsorption stability of zirconium is:
[0024] Since the common zirconium-loaded defluorination resin fixes the zirconium ions on the resin by the chelation effect of the resin on the zirconium ions, when the zirconium ions are oxidized to zirconium oxide crystals, the chelation effect of the resin on the zirconium oxide will be weakened, making the zirconium easy to fall off; the present invention utilizes the stability of the polymer skeleton to mix fine zirconium oxide crystal powder into a polymer carrier with good mechanical properties, so that the zirconium oxide crystals are not easy to fall off the carrier.
[0025] Beneficial effects of the present invention:
[0026] The defluorination adsorbent prepared by the present invention has the characteristics of good appearance structure, long service life and high zirconium loading. Through a series of experiments, the defluorination adsorbent prepared by granulation can be repeatedly adsorbed and desorbed for more than 10 times without obvious "slag falling". Through digestion experiments, it can be found that after more than 10 cycles of repeated adsorption and desorption, the zirconium loading of the adsorbent is less than 30% different from that of the adsorbent without adsorption and desorption. The defluorination adsorbent prepared by drop molding can be repeatedly adsorbed and desorbed for more than 20 times without obvious "slag falling". Through digestion experiments, it can be found that after more than 20 cycles of repeated adsorption and desorption, the zirconium loading of the adsorbent is less than 10% different from that of the adsorbent without adsorption and desorption.
[0027] The drop molding method can make the zirconium oxide crystals evenly dispersed in the carrier, while the shot blasting method has a certain degree of unevenness. However, in terms of process realization and mass production, the shot blasting process is easier to achieve mass production than the drop molding process. DETAILED DESCRIPTION
[0028] A method for preparing a defluorination adsorbent, characterized in that it comprises the following steps:
[0029] 1) mixing zirconium oxychloride with hydrochloric acid solution and water, adjusting the pH value to 9.0 with sodium hydroxide solution at a drip rate of 10 mL / min, and drying to obtain zirconium oxide crystals;
[0030] The volume ratio of the zirconium oxychloride mass to the volume of the hydrochloric acid solution and the volume of water is 256 g:240 mL:500 mL;
[0031] 2) mixing an organic solvent with a polymer to obtain a polymer solution;
[0032] The polymer includes one or more of polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate and polysulfone;
[0033] The volume ratio of the organic solvent to the mass ratio of the polymer is 200 mL:50 g;
[0034] 3) mixing the zirconium oxide crystals obtained in step 1) with the polymer solution obtained in step 2) to obtain a mixture, and subjecting the mixture to drop molding or granulation to obtain a defluorination adsorbent;
[0035] The mass ratio of the zirconium oxide crystals to the polymer in step 2) is 2 to 50:5.
[0036] The present invention mixes zirconium oxychloride with hydrochloric acid solution and water, uses sodium hydroxide solution to adjust the pH value to 9.0 at a drip rate of 10 mL / min, and obtains zirconium oxide crystals after drying; the mass ratio of the zirconium oxychloride to the volume of the hydrochloric acid solution and the volume of water is 256 g: 240 mL: 500 mL. This step is to obtain a good crystal structure so that the zirconium oxide crystals prepared by the present invention have good fluorine adsorption. The present invention is preferably washed with distilled water and alcohol before drying. The present invention has no special restrictions on the washing, and those skilled in the art can use conventional methods. In the present invention, the drying conditions preferably include: a temperature of 90°C and a time of preferably 20 hours. The present invention is preferably crushed into powder after drying and then used. In the present invention, the zirconium oxychloride is preferably zirconium oxychloride octahydrate. In the present invention, the mass percentage of the hydrochloric acid solution is preferably 30%. In the present invention, the mass percentage of the sodium hydroxide solution is preferably 30%. In the present invention, the adjusted temperature is preferably 60°C.
[0037] The present invention mixes an organic solvent with a polymer to obtain a polymer solution; the polymer includes one or more of polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate and polysulfone; the volume ratio of the organic solvent to the mass ratio of the polymer is 200mL:50g. In the present invention, the organic solvent preferably includes acetone and / or dimethylformamide. In the present invention, the mixing temperature is preferably 50°C.
[0038] The present invention mixes the obtained zirconium oxide crystals with the obtained polymer solution to obtain a mixture, and the mixture is subjected to drop molding or granulation to obtain a defluorination adsorbent; the mass ratio of the zirconium oxide crystals to the polymer is 2:5.
[0039] In the present invention, the drip molding preferably includes the following steps: passing the mixture into water through a pinhole with a diameter of 0.5 mm, washing with water and drying at 80° C. to obtain a defluorination adsorbent. The present invention has no special limitation on the washing, and those skilled in the art can perform conventional operations.
[0040] In the present invention, the granulation preferably includes the following steps: the mixture is made into spherical particles with a particle size of 0.5 to 1 mm, and then solidified, cleaned and dried to obtain a defluorination adsorbent. In the present invention, the solidification conditions preferably include: mixing and solidifying the spherical particles with a poor solvent. In the present invention, the poor solvent is preferably a solvent insoluble in the polymer skeleton, such as water; in the present invention, the solidification conditions are preferably room temperature. The present invention preferably uses pure water and alcohol for cleaning. The present invention has no special limitation on cleaning, and those skilled in the art can use conventional methods.
[0041] The present invention also provides a defluorination adsorbent prepared by the preparation method described in the above technical solution.
[0042] The present invention also provides the use of the defluorination adsorbent described in the above technical solution in improving the stability of zirconium adsorption by the adsorbent.
[0043] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0044] Example 1
[0045] A method for preparing a defluorination adsorbent, comprising the following steps:
[0046] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0047] (2) Add 200 ml of acetone and 50 g of polyvinyl chloride (molecular weight 50,000 Da), heat to 50° C. and stir until the polyvinyl chloride is completely dissolved.
[0048] (3) Add 500 g of the zirconium oxide crystals obtained in step (1) to the polyvinyl chloride solution prepared in step (2), mix thoroughly, and allow the solution to be fully dispersed in the zirconium oxide crystals to have a certain viscosity.
[0049] (4) The mixture from (3) is put into a granulator to prepare cylindrical granules with a particle size of 0.5-1.0 mm.
[0050] (5) The granules prepared in (4) are placed into a spheronizer to form spherical granules.
[0051] (6) The spherical particles (5) are placed into a poor solvent (such as water) of the polymer carrier, and are completely solidified at room temperature. The particles are then washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solids are dried in an oven at 80°C to obtain a defluorination adsorbent.
[0052] After digestion analysis (i.e., the polymer carrier is digested cleanly by combustion, and then the remaining zirconium oxide crystals are tested), the zirconium loading of the defluorination adsorbent is 657.6 mg / g, and after 10 adsorption and desorption cycles, its zirconium loading is 503.7 mg / g after the experiment.
[0053] 1. Use a measuring cylinder to measure 60 ml of adsorbent and fill it into the glass exchange column. There should be no bubbles in the adsorbent layer and a 5 cm high water cushion should be maintained on the adsorbent layer.
[0054] 2. Use 4BV of 5% sulfuric acid at 2BV / h to regenerate the adsorbent layer from top to bottom, and rinse with 4BV of pure water.
[0055] 3. Run the nickel sulfate solution through the adsorbent from top to bottom at a flow rate of 4 BV / h, collect the effluent, and take samples every 2 hours to test the F concentration and pH until the effluent F concentration is ≥5 mg / L. Continue to take samples every 2 hours to test the F concentration and pH until the adsorbent is saturated.
[0056] Example 2
[0057] A method for preparing a defluorination adsorbent, comprising the following steps:
[0058] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0059] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polyethylene terephthalate (molecular weight 50,000 Da), heat to 50° C. and stir until the PET is completely dissolved.
[0060] (3) Add 500 g of the zirconium oxide crystals obtained in step (1) to the PET solution prepared in step (2), mix thoroughly, and allow the solution to be fully dispersed in the zirconium oxide crystals to have a certain viscosity.
[0061] (4) The mixture from (3) is put into a granulator to prepare cylindrical granules with a particle size of 0.5-1.0 mm.
[0062] (5) The granules prepared in (4) are placed into a spheronizer to form spherical granules.
[0063] (6) The spherical particles (5) are placed into a poor solvent (such as water) of the polymer carrier, and are completely solidified at room temperature. The particles are then washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solids are dried in an oven at 80°C to obtain a defluorination adsorbent.
[0064] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 632.8 mg / g, and after 10 adsorption and desorption cycle experiments, the zirconium loading was 512.3 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0065] Example 3
[0066] A method for preparing a defluorination adsorbent, comprising the following steps:
[0067] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0068] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polybutylene terephthalate (molecular weight 75,000 Da), heat to 50° C. and stir until the PBT is completely dissolved.
[0069] (3) Add 500 g of the zirconium oxide crystals obtained in step (1) to the polybutylene terephthalate solution prepared in step (2), and mix thoroughly to allow the solution to be fully dispersed in the zirconium oxide crystals and to have a certain viscosity.
[0070] (4) The mixture from (3) is put into a granulator to prepare cylindrical granules with a particle size of 0.5-1.0 mm.
[0071] (5) The granules prepared in (4) are placed into a spheronizer to form spherical granules.
[0072] (6) The spherical particles (5) are placed into a poor solvent (such as water) of the polymer carrier, and are completely solidified at room temperature. The particles are then washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solids are dried in an oven at 80°C to obtain a defluorination adsorbent.
[0073] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 680.4 mg / g, and after 10 adsorption and desorption cycle experiments, the zirconium loading was 550.6 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0074] Example 4
[0075] A method for preparing a defluorination adsorbent, comprising the following steps:
[0076] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0077] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polysulfone (molecular weight 50,000 Da), heat to 50° C. and stir until the polysulfone is completely dissolved.
[0078] (3) Add 500 g of the defluorination adsorbent core to the polysulfone solution prepared in (2), mix thoroughly, and allow the solution to be fully dispersed in the zirconium oxide crystals to have a certain viscosity.
[0079] (4) The mixture from (3) is put into a granulator to prepare cylindrical granules with a particle size of 0.5-1.0 mm.
[0080] (5) The granules prepared in (4) are placed into a spheronizer to form spherical granules.
[0081] (6) The spherical particles (5) are placed in a poor solvent (such as water) of the polymer carrier, and are completely solidified at room temperature. The particles are then washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solids are dried in an oven at 80°C to obtain a defluorination adsorbent.
[0082] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 674.3 mg / g, and after 10 adsorption and desorption cycle experiments, the zirconium loading was 532.3 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0083] Example 5
[0084] A method for preparing a defluorination adsorbent, comprising the following steps:
[0085] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0086] (2) Add 200 ml of acetone and 50 g of polyvinyl chloride (molecular weight 50,000 Da), heat to 50° C. and stir until the polyvinyl chloride is completely dissolved.
[0087] (3) Add 20 g of the zirconium oxide crystals obtained in step (1) to the polyvinyl chloride solution prepared in step (2), and stir thoroughly to allow the zirconium oxide crystals to be fully dispersed in the solution while maintaining a certain fluidity.
[0088] (4) Slowly drain the liquid prepared in (3) and allow it to pass through a pinhole with a diameter of 0.5 mm into water, so that it can be dripped into the desired spherical defluorination adsorbent.
[0089] (5) The spherical defluorination adsorbent prepared in (4) is first washed three times with pure water and then washed twice with alcohol, and finally washed with pure water. The washed solid is dried in an oven at 80° C. to obtain a defluorination adsorbent.
[0090] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 190 mg / g, and after 20 adsorption and desorption cycle experiments, the zirconium loading was 181 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0091] Example 6
[0092] A method for preparing a defluorination adsorbent, comprising the following steps:
[0093] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0094] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polyethylene terephthalate (molecular weight 50,000 Da), heat to 50° C. and stir until the PET is completely dissolved.
[0095] (3) Add 20 g of the zirconium oxide crystals obtained in step (1) to the polyethylene terephthalate solution prepared in step (2), and stir thoroughly to allow the zirconium oxide crystals to be fully dispersed in the solution while maintaining a certain fluidity.
[0096] (4) The liquid prepared in (3) is slowly discharged and passed into water through a pinhole with a diameter of 0.5 mm, so that the liquid is dripped into a spherical defluorination adsorbent.
[0097] (5) The spherical defluorination adsorbent prepared in (4) was washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solid was dried in an oven at 80° C. to obtain a defluorination adsorbent.
[0098] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 176 mg / g, and after 20 adsorption and desorption cycle experiments, the zirconium loading was 164 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0099] Example 7
[0100] A method for preparing a defluorination adsorbent, comprising the following steps:
[0101] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0102] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polybutylene terephthalate (molecular weight 75,000 Da), heat to 50° C. and stir until the PBT is completely dissolved.
[0103] (3) Add 20 g of the zirconium oxide crystals obtained in step (1) to the polybutylene terephthalate solution prepared in step (2), and stir thoroughly to allow the zirconium oxide crystals to be fully dispersed in the solution while maintaining a certain fluidity.
[0104] (4) The liquid prepared in (3) is slowly discharged and passed into water through a pinhole with a diameter of 0.5 mm, so that the liquid is dripped into a spherical defluorination adsorbent.
[0105] (5) The spherical defluorination adsorbent prepared in (4) was washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solid was dried in an oven at 80° C. to obtain a defluorination adsorbent.
[0106] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 181 mg / g, and after 20 adsorption and desorption cycle experiments, the zirconium loading was 170 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0107] Example 8
[0108] A method for preparing a defluorination adsorbent, comprising the following steps:
[0109] (1) Add 256g of zirconium oxychloride octahydrate and 240ml of 30% hydrochloric acid to 500ml of water, heat to 60°C and stir. Use a peristaltic pump to add 30% liquid caustic soda to the above solution at a rate of 10ml / min until the end pH is 9.0. Wash twice with distilled water and alcohol respectively, and dry the solid in an oven at 90°C for 20 hours. Chop the dried solid into powder to obtain zirconium oxide crystals with good adsorption of fluorine. The above are all mass percentages.
[0110] (2) Add 200 ml of N,N-dimethylformamide and 50 g of polysulfone (molecular weight 50,000 Da), heat to 50° C. and stir until the polysulfone is completely dissolved.
[0111] (3) Add 20 g of the zirconium oxide crystals obtained in step (1) to the polysulfone solution prepared in step (2), and stir thoroughly to allow the zirconium oxide crystals to be fully dispersed in the solution while maintaining a certain fluidity.
[0112] (4) The liquid prepared in (3) is slowly discharged and passed into water through a pinhole with a diameter of 0.5 mm, so that the liquid is dripped into a spherical defluorination adsorbent.
[0113] (5) The spherical defluorination adsorbent prepared in (4) was washed three times with pure water and twice with alcohol, and finally washed with pure water. The washed solid was dried in an oven at 80° C. to obtain a defluorination adsorbent.
[0114] After analysis, it was found that the zirconium loading of the defluorination adsorbent was 195 mg / g, and after 20 adsorption and desorption cycle experiments, the zirconium loading was 187 mg / g. The adsorption and desorption cycle experiments were the same as those in Example 1.
[0115] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a defluorination adsorbent, characterized in that: The following steps are involved: 1) mixing zirconium oxychloride with hydrochloric acid solution and water, adjusting the pH value to 9.0 with sodium hydroxide solution at a drip rate of 10 mL / min, and drying to obtain zirconium oxide crystals; The volume ratio of the zirconium oxychloride mass to the volume of the hydrochloric acid solution and the volume of water is 256 g:240 mL:500 mL; 2) mixing an organic solvent with a polymer to obtain a polymer solution; The polymer includes one or more of polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate and polysulfone; The volume ratio of the organic solvent to the mass ratio of the polymer is 200 mL:50 g; 3) mixing the zirconium oxide crystals obtained in step 1) with the polymer solution obtained in step 2) to obtain a mixture, and subjecting the mixture to drop molding or granulation to obtain a defluorination adsorbent; The mass ratio of the zirconium oxide crystals to the polymer in step 2) is 2 to 50:
5.
2. The preparation method according to claim 1, characterized in that: The mass percentage of the hydrochloric acid solution in step 1) is 30%.
3. The preparation method according to claim 1, characterized in that: The mass percentage of the sodium hydroxide solution in step 1) is 30%.
4. The preparation method according to claim 1, characterized in that: The temperature adjusted in step 1) is 60°C.
5. The preparation method according to claim 1, characterized in that: The organic solvent in step 2) includes acetone and / or dimethylformamide.
6. The preparation method according to claim 1, characterized in that: The step 3) drip molding comprises the following steps: the mixture is passed through a pinhole with a diameter of 0.5 mm into water, and after washing and drying, a defluorination adsorbent is obtained.
7. The preparation method according to claim 1, characterized in that: The step 3) granulation comprises the following steps: the mixture is made into spherical particles with a particle size of 0.5 to 1 mm, and then solidified, cleaned and dried to obtain a defluorination adsorbent.
8. The preparation method according to claim 7, characterized in that: The solidification conditions include: mixing the spherical particles with a poor solvent and solidifying them.
9. A defluorination adsorbent prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the defluorination adsorbent according to claim 9 in improving the stability of zirconium adsorption by the adsorbent.